2011
DOI: 10.1242/jeb.057349
|View full text |Cite
|
Sign up to set email alerts
|

Potentially adaptive effects of maternal nutrition during gestation on offspring phenotype of a viviparous reptile

Abstract: SUMMARY Viviparous reptiles have been used as model species for many studies that seek to explain the evolution of viviparity. The vast majority of such studies have focused on the advantage viviparity provides with regards to maternal control of embryonic developmental temperature. However, viviparity may also allow increased control of nutrient transfer, such that mothers adaptively manipulate offspring phenotype through varying maternal nutritional support. Because maternal nutritional transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Maternal thermoregulation during gestation is thought to allow the maintenance of stable developmental temperatures (Shine, 1995) and/or to provide a buffer to embryos from unsuitable developmental temperatures (Kearney et al, 2009) as well as potentially provide fitness benefits to females through, for example, reduced basking length and the costs associated with reproduction (Schwarzkopf and Shine, 1991;Schwarzkopf and Andrews, 2012a;Schwarzkopf and Andrews, 2012b;Shine, 2012). Maternal manipulation of the offspring environment may also potentially allow females to 'pre-programme' offspring phenotype to better suit the environment the offspring will encounter (or be born into) (Marshall and Uller, 2007;Cadby et al, 2010a;Pen et al, 2010;Cadby et al, 2011;Uller et al, 2011). Maternal 'pre-programming' to future developmental temperatures could occur through maternal manipulation of offspring phenotype to fit the predicted environment and/or through embryonic acclimation to the thermal conditions experienced during development (Seebacher, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal thermoregulation during gestation is thought to allow the maintenance of stable developmental temperatures (Shine, 1995) and/or to provide a buffer to embryos from unsuitable developmental temperatures (Kearney et al, 2009) as well as potentially provide fitness benefits to females through, for example, reduced basking length and the costs associated with reproduction (Schwarzkopf and Shine, 1991;Schwarzkopf and Andrews, 2012a;Schwarzkopf and Andrews, 2012b;Shine, 2012). Maternal manipulation of the offspring environment may also potentially allow females to 'pre-programme' offspring phenotype to better suit the environment the offspring will encounter (or be born into) (Marshall and Uller, 2007;Cadby et al, 2010a;Pen et al, 2010;Cadby et al, 2011;Uller et al, 2011). Maternal 'pre-programming' to future developmental temperatures could occur through maternal manipulation of offspring phenotype to fit the predicted environment and/or through embryonic acclimation to the thermal conditions experienced during development (Seebacher, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that P. entrecasteauxii may be able to simultaneously maintain their own body condition and allocate energy for embryonic development during gestation (ITONAGA et al 2012a; also see CADBY et al 2011). Indeed, WAPSTRA & SWAIN (2001 found that abdominal fat body mass in a sympatric viviparous reptile, N. ocellatus, was higher at the end of pregnancy than in early and mid pregnancy, despite the fact that they also provide relatively large placental contributions to embryonic nutrition (THOMPSON et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Matrotrophy allows maternal effects on offspring phenotype to respond to more than one environmental factor [20], [22], in this case basking opportunity and/or food intake during gestation. Trade-offs between fitness costs and benefits related to maternal net energy availability during gestation may have been an important determinant for the evolution of matrotrophy in P. entrecasteauxii .…”
Section: Discussionmentioning
confidence: 99%
“…This model developed for fish has largely been ignored in studies of the evolution of viviparity and subsequent evolution of matrotrophy in reptiles. Past studies generally concentrated on the key selective force of maternal effects mediated through temperature [11], however maternal food availability may be important [20]–[22]. This is because in reptiles net energy gain is strongly associated with the interaction between body temperature and food intake [23], [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation